The effect of artificial diet on the production of alarm pheromone by Myzus persicae. (25th August 2014) - van Emden, Helmut F.; Dingley, Jane; Dewhirst, Sarah Y.; Pickett, John A.; Woodcock, Christine M.; Wadhams, Lester J.
Abstract The cornicle secretion of Myzus persicae reared on artificial diet only elicits an alarm response in plant‐reared conspecifics after the young aphids have been transferred to plants for 7 days. Acetate in the form of 0.32% sodium acetate has been added to the diet as an early step in synthesis of the alarm pheromone, (E)‐β‐farnesene (EBF). The cornicle secretion of diet‐reared aphids then elicits an alarm response. However, there is no difference in internal EBF concentration between plant‐ and diet‐reared aphids. Puncturing aphids, either plant‐ or diet‐reared, with a pin shows that both can elicit an alarm response, whereas it is reduced by half with diet‐reared individuals. Although there is no significant difference in the concentration of EBF produced, the total amount in diet‐reared aphids is increased by acetate in the diet to a level similar to that in plant‐reared individuals: the size of aphids reared on an acetate‐supplemented diet is increased and comparable with the size of those that are plant‐reared. Bioassays with a range of EBF concentrations show a high threshold for the alarm response. It is concluded that the different size of aphids reared on plants and standard diet results in them secreting, respectively, above and below the response threshold.